Babasaheb: The Unsung Hero and Uncrowned Mahatma of India - Guru Dev Teeluckdharry (Recent Research Advances in Arts and Social Studies Vol. 8, 2024)
Dr. Bhimrao Ramji Ambedkar also known as Babasaheb was the Father of the Indian Constitution. Dr. Bhimrao Ramji Ambedkar (born on 14th April 1891 and passed away on 6th December 1956) was an Indian barrister, economist, social reformer, educationist, polymath, visionary, freedom fighter, liberator, humanist and political leader who drafted the Constitution of India. Babasaheb was the real Mahatma of India. Babasaheb in fact recognized that his Western Education was an infallible pillar that allowed him to draft the constitution of modern India and as such he became known worldwide as the “Father of the Indian Constitution”. He also served as Law and Justice minister in the first cabinet of Jawaharlal Nehru, and was an unfathomable inspiration for the Dalits after renouncing Hinduism and embracing Buddhism. According to many historians he was more eminent than Mahatma Gandhi. But he is the unsung hero and uncrowned Mahatma of India due to his Dalit caste. Babasaheb recognised the immense and precious value of his Western Education that played a vital role in the upliftment and enshrinement of modern India. Unlike Mahatma Gandhi, he was a liberal Indian and never antagonized the Americans and Britishers.